Kierunki doskonalenia rachunku kosztów w polskich przedsiębiorstwach przemysłowych w XX wieku - Tatarska, Marzena (The Most Important Models of Calculating Costs and the Directions of Their Improvement, 2006)
In the article presented I brought forward the most important models of calculating costs, and the directions of their improvement, in relation to law, and socio-economic restrictions of the country. Moreover, I presented how the range of its new tasks broadened throughout the years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 11-28